Musicophilia: Tales of music and the brain - Sacks, Oliver (London Picador, 2007)
In chapters examining depressives and musical dreamers, this book succeeds not only in articulating the musical experience but in locating it in the human brain. It shows that music is not simply about sound, but also movement, visualization, and silence. It follows the experiences of patients drawn to or divorced from music.